Persepsi Siswa tentang Ekosistem Mangrove sebagai Sumber Belajar (Studi Pada Siswa X IPA SMAN di Kabupaten Gorontalo Utara) - Widia Rahma Tanti; Dewi Wahyuni K. Baderan; Ramli Utina (Pro-Life, 2021)
This study discusses how students' perceptions of the Mangrove ecosystem as a source of learning biology (a study of students in class X IPA SMAN in North Gorontalo district) ". This type of research is descriptive quantitative. Data collection was carried out by means of a survey which aims to obtain data about the facts contained in this research location using a questionnaire containing written statements that will be distributed online via google form to respondents to be answered. The target of this research is the students of class X IPA of SMAN 2 Gorontalo Utara and students of class X IPA of SMAN 6 Gorontalo Utara, amounting to 1 class each. This research was conducted for 1 week. The research data were obtained from a percentage questionnaire and analyzed using the Likert score assessment criteria. The results showed that the average answers from students showed that the students' perceptions of SMAN 2 Gorontalo Utara and SMAN 6 Gorontalo Utara towards the Mangrove ecosystem which was used as a learning resource for biology, gave a very agreeable response by looking at the average answer scores, namely 4.30 and 4. , 28, while for the percentage value the average result gets a value of 78% -89% with very good category.